High-toughness damping PVC (polyvinyl chloride) aggregate and application thereof in automobile sealing strip
By introducing PU/PA composite toughener and nano-silica modified CPE in PVC, the problem of insufficient toughness and shock absorption of PVC seal strips is solved, significantly improving its performance in different environments, suitable for automobiles Seal strips and other applications.
Patent Information
- Application Number
- CN202411490634.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing PVC automotive seal strips have problems such as poor toughness, poor shock absorption, and poor sealing effect in extreme environments.
Using high-toughness shock-absorbing PVC pellets, including PVC, PU/PA composite toughening agent and nano-silica modified CPE, the PVC is improved by blending PU/PA composite toughening agent and nano-silica modified CPE. toughness and shock absorption performance.
It significantly improves the tensile strength, bending strength, thermal stability and impact resistance of PVC pellets, enhances its performance at low temperatures, and meets the high toughness and shock absorption requirements of automotive seal strips.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing materials, and in particular to a high-toughness shock-absorbing PVC granular material and application thereof in automobile sealing strips. Background Art
[0002] As people's living standards continue to improve, the demand for comfort and safety of cars is also getting higher and higher. The sealing performance of vehicles has also been paid special attention to and has become a key factor in judging the quality of the whole vehicle. Automobile sealing strip products are one of the important parts that determine the quality of this indicator. They are widely used in the front and rear windshields, doors, windows, engine compartments, trunks and other parts of the car body to fill the gaps between the body parts. They have the functions of shock absorption, waterproofing, dustproofing, sound insulation, and decoration, and play a protective role for drivers and passengers and the whole vehicle. There are many types of automobile sealing strip products. According to the name classification of the installation parts (components), they include engine compartment sealing strips, front and rear windshield sealing strips, door frame sealing strips, door sealing strips, door glass guide groove sealing strips, door lower dust strips, door window sill inner and outer sealing strips, side window sealing strips, sunroof sealing strips, roof cover sealing strips, trunk (luggage box) sealing strips, etc. At present, there are four main types of automotive sealing strip materials: polyvinyl chloride (PVC) sealing strips, ethylene propylene diene monomer (EPDM) sealing strips, thermoplastic vulcanizate (TPV) sealing strips, and thermoplastic elastomer (TPE) sealing strips. Among them, PVC sealing strip materials have good processing performance, low manufacturing cost, and good characteristics such as corrosion resistance and insulation.
[0003] Polyvinyl chloride is a universal material with a high cost-effectiveness. Its outstanding advantages are flame retardancy, wear resistance, chemical corrosion resistance, low gas and water vapor leakage, and good comprehensive mechanical properties, product transparency, electrical insulation, heat insulation, sound absorption, and shock absorption. However, polyvinyl chloride has the defects of poor thermal stability and impact resistance. The notched impact strength of pure rigid polyvinyl chloride is only 3-5KJ / m 2PVC is a hard and brittle material, especially with poor low-temperature toughness. It quickly hardens and becomes brittle when the temperature is lowered, and it is very easy to crack when impacted. At present, the methods for strengthening and toughening PVC materials can be divided into two categories: chemical modification and physical modification. Chemical modification mainly introduces flexible (rigid) segments on the molecular chain of PVC by molecular design through grafting or copolymerization, so as to achieve the purpose of strengthening and toughening, but it has been restricted by economic and technical aspects, and its development speed is relatively slow; physical modification mainly refers to the melt blending modification of PVC and other materials (elastic particles, non-elastic particles, inorganic rigid particles / elastic particles composite), which is a simple, convenient, effective and low-cost method for strengthening and toughening PVC materials, but different types of toughening materials have certain differences in the degree to which they improve the performance of polymer materials. Therefore, the existing PVC sealing strips still have defects such as poor friction resistance, poor fatigue resistance, narrow processing temperature range, extremely low resilience, low tensile strength and low elongation at break. Therefore, how to prepare a PVC automotive sealing strip with high toughness and excellent shock absorption effect has become a problem to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a high-toughness shock-absorbing PVC granular material and its application in automobile sealing strips to solve the following technical problems: Existing PVC automotive sealing strips have the problems of poor toughness, poor shock absorption effect, and poor sealing effect in extreme environments.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-toughness shock-absorbing PVC granular material comprises at least the following raw materials in parts by weight: PVC 60-80; PU / PA composite toughening agent 5-15; Nano-silica modified CPE 10-20; Stabilizer 2-4; Antioxidant 0.05-1; UV absorber 0.1-0.5; Lubricant 0.1-1; Colorant 0.5-1; Processing aids 1-5.
[0006] As a further solution of the present invention: the preparation method of the PU / PA composite toughening agent comprises at least the following steps: The polyether is heated to 70-90°C under the protection of N2, toluene diisocyanate and N,N-dimethylpropionamide are added for reaction, and when the temperature is lowered to 40-600°C, triethanolamine is added for neutralization and salt formation, and 1,4-butanediol is added for chain extension, and then the PU emulsion is obtained by dispersion and emulsification; Sodium dodecyl sulfate, distilled water, part of butyl acrylate and part of crosslinking agent are mixed, heated to 60-80°C under the protection of N2, potassium persulfate is added, and the system is kept warm for 1-2 hours after turning blue, and then the remaining butyl acrylate monomer and the remaining crosslinking agent are added dropwise, and then the initiator and emulsifier are added, and the reaction is terminated after keeping warm for 2-4 hours to obtain PA emulsion; The PU emulsion and the PA emulsion are mixed, and then potassium persulfate, sodium dodecyl sulfate and distilled water are added and stirred evenly. After adjusting the pH value to 9-11 with NaOH solution, the mixture is added into a polymerization kettle, and the reaction system is sealed, decompressed, filled with nitrogen, and vented. After repeating the operation 3-5 times, the PU / PA composite toughening agent is obtained.
[0007] As a further solution of the present invention: the mass ratio of the PU emulsion to the PA emulsion is 1:1-3, and the volume ratio of the cross-linking agent to the butyl acrylate is 1:90-120.
[0008] As a further solution of the present invention: the preparation method of the nano-silicon dioxide modified CPE comprises at least the following steps: In the reaction kettle, add deionized water and emulsifier, add CPE powder under stirring, stir and emulsify to obtain a uniform dispersion; A mixture of 3-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:3-5 is uniformly dripped into the uniform dispersion, and after the dripping is completed, stirring is continued to react, and then hydrochloric acid is dripped to adjust the pH value to 2-3, and heated to 70-90° C. for reaction for 2-4 hours. After the reaction is completed, the temperature is lowered to 40-50° C., and the material is discharged, filtered, washed, deacidified, centrifuged, and dried to obtain the nano-silica modified CPE.
[0009] As a further solution of the present invention: the antioxidant is antioxidant 1076 or antioxidant 1010, and the colorant is carbon black.
[0010] As a further embodiment of the present invention: the ultraviolet light absorber is at least one of 2-hydroxy-4-methoxybenzophenone or 2-(2'-hydroxyphenyl-5'-methylphenyl)benzotriazole UV-P.
[0011] As a further embodiment of the present invention: the stabilizer is at least one of calcium stearate, calcium ricinoleate, zinc stearate, zinc ricinoleate or epoxidized soybean oil.
[0012] As a further embodiment of the present invention: the lubricant is butyl stearate or paraffin.
[0013] As a further solution of the present invention: the processing aid comprises at least an acrylic acid ester polymer Application of the high-toughness shock-absorbing PVC granules as described in any one of the above in automobile sealing strips.
[0014] Beneficial effects of the present invention: This application uses PU / PA composite toughening agent and nano-silicon dioxide modified CPE to toughen PVC to prepare PVC granules with flame retardancy, wear resistance, chemical corrosion resistance, low gas and water vapor leakage, comprehensive mechanical properties, heat insulation, sound insulation, shock absorption and high toughness, and increases the thermal stability, weather resistance and impact resistance of PVC granules. The high-toughness shock-absorbing PVC granules prepared by the present invention have the characteristics of excellent mechanical properties, high cost performance, and a wide range of applications, and are suitable for use in industries such as automobiles, construction, wires and cables, and household appliances.
[0015] In the present application, the CPE modified by nano-silicon dioxide is mixed with PVC, and the tensile strength, bending strength, bending modulus and heat deformation temperature of the obtained PVC granules are significantly improved. CPE has good chemical stability and a series of excellent characteristics, such as weather resistance, oil resistance, aging resistance and chemical resistance, and the molecular chain of CPE contains chlorine atoms, so it also has good flame retardant properties. CPE modified by nano-silicon dioxide, the small size effect and macroscopic quantum tunneling effect of silicon dioxide will make it produce percolation effect to penetrate into the vicinity of the unsaturated bond of rubber and act with the electron cloud of the unsaturated bond, thereby greatly improving the heat, light and chemical stability of rubber to achieve the purpose of improving the aging resistance and chemical resistance of the product. Therefore, nano-silicon dioxide is still used at high temperature to have the characteristics of high strength, high toughness and good stability, and the nano-silicon dioxide agglomerates are fully and evenly dispersed in the matrix material to form a "chain" through the preparation method in the present application, and then combined with rubber macromolecules to form a three-dimensional network structure, which can greatly improve the strength, elasticity and wear resistance of rubber products, reduce the performance reduction rate after rubber aging, and increase its weather resistance. In the present application, nano-silica modified CPE is blended with PVC. On the one hand, CPE can improve the tensile strength, flexural strength, flexural modulus and thermal stability of PVC pellets. On the other hand, nano-silica also has a toughening effect on PVC, and nano-silica is mainly distributed in CPE, which can also improve the toughening effect of CPE on PVC.
[0016] In this application, a PU / PA composite toughening agent is also prepared to toughen PVC, which improves the notched impact strength and low temperature resistance of the prepared PVC pellets. PU contains functional groups such as carbamate (-NHCOO-). Using PU to toughen PVC can improve the low temperature performance, physical and mechanical properties, elasticity, oil resistance, fatigue resistance, wear resistance and other properties of PVC, but the high temperature performance is not ideal. Using PA to toughen PVC can improve the advantages of PVC such as high mechanical strength, acid and alkali resistance, good weather resistance and light retention, but at the same time it has the disadvantage of "hot sticky and cold brittle". The preparation of PU / PA composite toughening agent, the addition of PA makes up for the defect of poor mechanical properties of PU. When the ratio of PU / PA is set within a certain range, the two rely on the polar hydrogen atoms of the PU urethane bond to form hydrogen bonds with the oxygen atoms on the ester group in the PA segment, and can penetrate each other and be well compatible. In addition, the polarity of polyether PU is weaker, the soft segment content is increased, the molecular order is reduced, and the flexibility of the soft segment is fully utilized, so that the notched impact strength of PVC is increased, the long-term compression deformation rate is reduced, and the tensile strength is improved. The product has vibration resistance and silent functions, and is used in automotive sealing strips to achieve good shock-absorbing and noise-reducing effects. DETAILED DESCRIPTION
[0017] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 The preparation method of PU / PA composite toughening agent comprises the following steps: 90g of polyether was added to a 250mL four-necked bottle equipped with a stirrer, a thermometer, a reflux condenser and a N2 blowing device, and heated to 80°C under N2 protection, and then 15g of toluene diisocyanate and 6g of N,N-dimethylpropionamide were added. After a period of reaction, triethanolamine was added to neutralize the salt when the system was cooled to 50°C, and 14-butanediol was added to extend the chain, and then dispersed and emulsified to obtain a PU emulsion; In a 250mL four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a N2 blowing device, 0.5g of sodium dodecyl sulfate and 200mL of distilled water were added, and 18g of butyl acrylate and a cross-linking agent of 1% of butyl acrylate monomer were added, and heated to 60°C under the protection of N2, and potassium persulfate was added. After the system turned blue, the reaction was kept warm for 1h, and then 70g of butyl acrylate monomer and a cross-linking agent of 1% of butyl acrylate monomer were added dropwise, and the reaction was terminated after keeping warm for 2h to obtain a PA emulsion; The PU emulsion and PA emulsion prepared above were mixed in a mass ratio of 1:1.5, and then potassium persulfate, sodium dodecyl sulfate and distilled water were added and stirred evenly. The pH value was adjusted to 9-11 with NaOH solution, and added into a 2L polymerization kettle. The reaction system was sealed, decompressed, filled with nitrogen, and vented. After repeating the operation 3 times, a PU / PA composite emulsion, i.e., a PU / PA composite toughening agent, was obtained.
[0019] The preparation method of nano-silicon dioxide modified CPE comprises at least the following steps: Add 3000g of deionized water and 0.5g of sodium dodecylbenzene sulfonate into a 50L enamel reactor, add 500g of chlorinated polyethylene powder under stirring, and stir for 30min to emulsify and disperse the chlorinated polyethylene in water to form a uniform dispersion; Weigh 5 g of a mixture of tetramethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 4:1, place it in a dropping funnel, and uniformly add it dropwise to the aqueous dispersion of chlorinated polyethylene for 1 hour. After the dropping is completed, continue stirring for 1 hour, then add 1M hydrochloric acid dropwise to adjust the pH value to 3, heat to 80°C, continue to react for 2 hours, cool to 50°C, discharge the material, repeatedly wash with distilled water for deacidification until the filtrate is neutral, centrifuge, and then place in a 60°C vacuum drying oven to dry to constant weight to obtain nano-silica modified CPE.
[0020] A method for preparing high-toughness shock-absorbing PVC granules comprises at least the following steps: 70 parts of polyethylene monomer were mixed with 10 parts of the PU / PA composite emulsion obtained above, and polymerized at 50°C±0.5°C. When the pressure in the autoclave dropped to 0.3MPa, the reaction was terminated by rapid cooling. The obtained emulsion was frozen at -20°C for 16-20h, demulsified, filtered, washed and dried to obtain PU / PA composite toughened PVC resin powder. The PU / PA composite toughened PVC resin powder, 2 parts of stabilizer calcium stearate, 0.3 parts of lubricant butyl stearate, 1 part of colorant carbon black and 2 parts of processing aid acrylic polymer were placed in a high-speed stirrer and stirred at a speed of 500 rpm for 30 minutes; Then, 14 parts of nano-silica modified CPE were added to the above-mentioned high-speed stirrer, mixed evenly and added to the reactor, inert gas was introduced to replace the air in the reactor, and then the temperature was raised to 100°C at a heating rate of 1°C / min under stirring and maintained for 20 minutes, and then naturally dropped to 70°C under stirring, the pressure in the reactor was adjusted to normal pressure, and then 0.3 parts of antioxidant 1010 and 0.4 parts of ultraviolet light absorber 2-hydroxy-4-methoxybenzophenone were added, stirred for 15 minutes, and naturally dropped to room temperature; The product is then extruded through a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 60 mm, the aspect ratio is 36, and the extrusion temperature is 170° C., to obtain high-toughness shock-absorbing PVC pellets for automobile sealing strips.
[0021] Example 2 In the preparation step of the PU / PA composite toughening agent, the prepared PU emulsion and PA emulsion are mixed in a mass ratio of 1:3, and the remaining components and methods are the same as those in Example 1.
[0022] The components and preparation method of the nano-silica modified CPE are the same as those in Example 1.
[0023] In the preparation steps of a high-toughness shock-absorbing PVC granule, only the PU / PA composite toughening agent added to the high-toughness shock-absorbing PVC granule component in Example 1 is replaced with the PU / PA composite toughening agent prepared in Example 2, and the other components and preparation method are the same as Example 1.
[0024] Example 3 In the preparation step of nano-silica modified CPE, 500 g of chlorinated polyethylene powder and 10 g of a mixture of tetramethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 4:1 were weighed, and the remaining components and preparation method were the same as those in Example 1.
[0025] The components and preparation method of the PU / PA composite toughening agent are the same as those in Example 1.
[0026] In the preparation steps of a high-toughness shock-absorbing PVC granule, only the nano-silicon dioxide-modified CPE added to the high-toughness shock-absorbing PVC granule component in Example 1 is replaced with the nano-silicon dioxide-modified CPE prepared in Example 3, and the other components and preparation methods are the same as those in Example 1.
[0027] Example 4 A method for preparing high-toughness shock-absorbing PVC granules comprises at least the following steps: 65 parts of polyethylene monomer were mixed with 12 parts of the PU / PA composite emulsion prepared in Example 1, and polymerized at 50°C±0.5°C. When the pressure in the autoclave dropped to 0.3 MPa, the reaction was terminated by rapid cooling. The obtained emulsion was frozen at -20°C for 16-20 hours, demulsified, filtered, washed and dried to obtain PU / PA composite toughened PVC resin powder. The PU / PA composite toughened PVC resin powder, 2 parts of stabilizer calcium stearate, 0.3 parts of lubricant butyl stearate, 1 part of colorant carbon black and 3 parts of processing aid acrylic polymer were placed in a high-speed stirrer and stirred at a speed of 500 rpm for 30 minutes; Then, 16 portions of the nano-silicon dioxide modified CPE prepared in Example 1 were added to the high-speed stirrer, mixed evenly, and added to the reactor, and inert gas was introduced to replace the air in the reactor. Then, the temperature was raised to 100°C at a rate of 1°C / min under stirring and maintained for 20 minutes, then naturally dropped to 70°C under stirring, the pressure in the reactor was adjusted to normal pressure, and then 0.3 parts of antioxidant 1010 and 0.4 parts of ultraviolet light absorber 2-hydroxy-4-methoxybenzophenone were added, stirred for 15 minutes, and naturally dropped to room temperature; The mixture is then extruded through a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 60 mm, the aspect ratio is 36, and the extrusion temperature is 180° C., to obtain high-toughness shock-absorbing PVC pellets for automobile sealing strips.
[0028] Comparative Example 1 The preparation steps of the PU / PA composite toughening agent are omitted.
[0029] The components and preparation method of the nano-silica modified CPE are the same as those in Example 1.
[0030] A method for preparing high-toughness shock-absorbing PVC granules comprises at least the following steps: 70 parts of PVC, 2 parts of stabilizer calcium stearate, 0.3 parts of lubricant butyl stearate, 1 part of colorant carbon black and 2 parts of processing aid acrylic polymer were placed in a high-speed stirrer and stirred and mixed at a speed of 500 rpm for 30 minutes; Then, 10 parts of PU resin and 14 parts of nano-silicon dioxide modified CPE were added to the above-mentioned high-speed stirrer, mixed evenly and added to the reactor, inert gas was introduced to replace the air in the reactor, and then the temperature was raised to 100°C at a heating rate of 1°C / min under stirring and maintained for 20 minutes, and then naturally dropped to 70°C under stirring, the pressure in the reactor was adjusted to normal pressure, and then 0.3 parts of antioxidant 1010 and 0.4 parts of ultraviolet light absorber 2-hydroxy-4-methoxybenzophenone were added, stirred for 15 minutes, and naturally dropped to room temperature; The granules are then extruded through a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 60 mm, the aspect ratio is 36, and the extrusion temperature is 170° C. to obtain PVC pellets for automobile sealing strips.
[0031] Comparative Example 2 The preparation steps of PU / PA composite toughening agent are omitted.
[0032] The components and preparation method of the nano-silica modified CPE are the same as those in Example 1.
[0033] In the preparation steps of a high-toughness shock-absorbing PVC granule, only the PU resin added in the high-toughness shock-absorbing PVC granule component in Comparative Example 1 is replaced with an equal amount of PA elastomer, and the remaining components and preparation method are the same as those in Comparative Example 1.
[0034] Comparative Example 3 The preparation step of nano-silica modified CPE is omitted.
[0035] The components and preparation method of the PU / PA composite toughening agent are the same as those in Example 1.
[0036] In the preparation step of a high-toughness shock-absorbing PVC granule, 500 g of chlorinated polyethylene powder is directly weighed to replace the nano-silicon dioxide-modified CPE, and the remaining components and preparation method are the same as those in Example 1.
[0037] Comparative Example 4 The preparation step of nano-silica modified CPE is omitted.
[0038] The components and preparation method of the PU / PA composite toughening agent are the same as those in Example 1.
[0039] In the preparation step of a high-toughness shock-absorbing PVC granule, nano-silicon dioxide-modified CPE is not added, and the remaining components and preparation method are the same as those in Example 1.
[0040] Performance Testing The tensile properties were tested in accordance with GB / T3923.1-1997, and the tensile strength at -40℃, room temperature and 80℃ was tested respectively, and the tensile rate was 60mm / min; the bending properties were tested in accordance with GB / T9341-200; the simply supported beam impact strength and the retention rate of the simply supported beam notched impact strength under the condition of artificial weathering for 6000h were tested in accordance with "Determination of the impact strength of simply supported beams of plastics ISO179-2000". The test results are shown in the following table:
[0041] It can be seen from the above table that the PVC pellets obtained after toughening with the PU / PA composite toughening agent and nano-silicon dioxide modified CPE in Examples 1-4 of the present invention have good tensile strength, flexural strength and impact strength at low temperature, room temperature and high temperature, and have excellent notched impact strength and weather resistance, and can meet the use requirements of high toughness, shock absorption and sealing of automotive sealing strips under different conditions. In Comparative Example 1, a PU toughening agent is prepared instead of a PU / PA composite toughening agent, and in Comparative Example 2, a PA toughening agent is prepared instead of a PU / PA composite toughening agent. In Comparative Example 3, CPE is not modified with nano-silicon dioxide, and PVC is directly toughened with CPE. In Comparative Example 4, the preparation of nano-silicon dioxide-modified CPE is omitted, that is, only PVC is toughened with a PU / PA composite toughening agent. The measured tensile strength, flexural strength and impact strength are significantly reduced, and the tensile strength and notched impact strength at high temperature in Comparative Example 1 are significantly reduced, while the tensile strength and notched impact strength at low temperature in Comparative Example 2 are significantly reduced. The tensile strength and flexural strength in Comparative Examples 3 and 4 are also reduced, and the reduction in Comparative Example 4 is obvious, indicating that toughening PVC with a PU / PA composite toughening agent can improve the notched impact strength of PVC pellets and the tensile strength under low and high temperature environments, and blending nano-silicon dioxide-modified CPE with PVC can improve the mechanical properties of PVC pellets.
[0042] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A high-toughness shock-absorbing PVC granular material, characterized in that: At least the following raw materials are included in parts by weight: PVC 60-80; PU / PA composite toughening agent 5-15; Nano-silica modified CPE 10-20; Stabilizer 2-4; Antioxidant 0.05-1; UV absorber 0.1-0.5; Lubricant 0.1-1; Colorant 0.5-1; Processing aids 1-5.
2. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The preparation method of the PU / PA composite toughening agent comprises at least the following steps: The polyether is heated to 70-90°C under the protection of N2, toluene diisocyanate and N,N-dimethylpropionamide are added for reaction, and when the temperature is lowered to 40-60°C, triethanolamine is added for neutralization to form salt, and 1,4-butanediol is added for chain extension, and then the PU emulsion is obtained by dispersion and emulsification; Sodium dodecyl sulfate, distilled water, part of butyl acrylate and part of crosslinking agent are mixed, heated to 60-80°C under the protection of N2, potassium persulfate is added, and the system is kept warm for 1-2 hours after turning blue, and then the remaining butyl acrylate monomer and the remaining crosslinking agent are added dropwise, and then the initiator and emulsifier are added, and the reaction is terminated after keeping warm for 2-4 hours to obtain PA emulsion; The PU emulsion and the PA emulsion are mixed, and then potassium persulfate, sodium dodecyl sulfate and distilled water are added and stirred evenly. After adjusting the pH value to 9-11 with NaOH solution, the mixture is added into a polymerization kettle, and the reaction system is sealed, decompressed, filled with nitrogen, and vented. After repeating the operation 3-5 times, the PU / PA composite toughening agent is obtained.
3. The high-toughness shock-absorbing PVC granules according to claim 2, characterized in that: The mass ratio of the PU emulsion to the PA emulsion is 1:1-3, and the volume ratio of the cross-linking agent to the butyl acrylate is 1:90-120.
4. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The preparation method of the nano-silicon dioxide modified CPE comprises at least the following steps: In the reaction kettle, add deionized water and emulsifier, add CPE powder under stirring, stir and emulsify to obtain a uniform dispersion; A mixture of 3-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:3-5 is uniformly dripped into the uniform dispersion, and after the dripping is completed, stirring is continued to react, and then hydrochloric acid is dripped to adjust the pH value to 2-3, and heated to 70-90° C. for reaction for 2-4 hours. After the reaction is completed, the temperature is lowered to 40-50° C., and the material is discharged, filtered, washed, deacidified, centrifuged, and dried to obtain the nano-silica modified CPE.
5. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The antioxidant is antioxidant 1076 or antioxidant 1010, and the colorant is carbon black.
6. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The ultraviolet light absorber is at least one of 2-hydroxy-4-methoxybenzophenone and 2-(2'-hydroxyphenyl-5'-methylphenyl)benzotriazole UV-P.
7. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The stabilizer is at least one of calcium stearate, calcium ricinoleate, zinc stearate, zinc ricinoleate or epoxidized soybean oil.
8. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The lubricant is butyl stearate or paraffin.
9. The high-toughness shock-absorbing PVC granules according to claim 1, characterized in that: The processing aid at least includes an acrylic polymer.
10. Use of the high-toughness shock-absorbing PVC granules as claimed in any one of claims 1 to 9 in automobile sealing strips.
